Methodology and uncertainty estimation for measurements of methane leakage in a manufactured house - A. Karion; M. F. Link; R. Robertson; R. Robertson; T. Boyle; D. Poppendieck (Atmospheric Measurement Techniques)
Methane emissions from natural gas appliances and infrastructure within buildings have historically not been captured in greenhouse gas inventories, leading to under-estimates, especially in urban areas. Recent measurements of these post-meter emissions have indicated non-negligible emissions within residences, with impacts on both indoor air quality and climate. As a result, methane losses from residential buildings have been included in the latest US national inventory, with emission factors determined from a single study of homes in California. To facilitate future additional studies investigating building methane emissions, we conducted a controlled experiment to document a methodology for such measurements and estimated associated uncertainties. We determined whole-house methane emission rates with a mass balance approach using near-simultaneous measurements of indoor and outdoor methane mole fractions at a manufactured house. We quantified the uncertainty in whole-house methane emission rates by varying the forced outdoor air ventilation rate of the manufactured house, measuring the outdoor air change rate using both sulfur hexafluoride and carbon dioxide tracers, and performing methane injections at prescribed rates. We found that the whole-house quiescent methane emission rate (i.e., emission rate when all gas appliances were off) in the manufactured house averaged 0.33 g d−1 with methodological errors in the calculated emission rates of approximately 19 % (root-mean-square deviation). We also measured the quiescent leakage from the manufactured house over 3 months to find 26 % (1σ) variability in emissions over two seasons. Our findings can be used to inform plans for future studies quantifying indoor methane losses downstream of residential meters using similar methods. Such quantification studies are sorely needed to better understand building methane emissions and their drivers to inform inventories and plan mitigation strategies.